A Novel Mechanism Underlies the Hepatotoxicity of Pyrazinamide - Shih, Tung-Yuan (American Society for Microbiology, 2013)
Relatively little is known about the hepatotoxicity of pyrazinamide (PZA). PZA requires activation by amidase to form pyrazinoic acid (PA). Xanthine oxidase then hydroxylates PA to form 5-hydroxypyrazinoic acid (5-OH-PA). PZA can also be directly oxidized to form 5-OH-PZA. Before this study, it was unclear which metabolic pathway or PZA metabolites led to hepatotoxicity. This study determines whether PZA metabolites are responsible for PZA-induced hepatotoxicity. PZA metabolites were identified and cytotoxicity in HepG2 cells was assessed. Potential PZA and PA hepatotoxicity was then tested in rats. Urine specimens were collected from 153 tuberculosis (TB) patients, and the results were evaluated to confirm whether a correlation existed between PZA metabolite concentrations and hepatotoxicity. This led to the hypothesis that coadministration of amidase inhibitor (bis-p-nitrophenyl phosphate [BNPP]) decreases or prevents PZA- and PZA metabolite-induced hepatotoxicity in rats. PA and 5-OH-PA are more toxic than PZA. Electron microscopy showed that PZA and PA treatment of rats significantly increases aspartate transaminase (AST) and alanine aminotransferase (ALT) activity and galactose single-point (GSP) levels (P < 0.005). PA and 5-OH-PA levels are also significantly correlated with hepatotoxicity in the urine of TB patients (P < 0.005). Amidase inhibitor, BNPP, decreases PZA-induced, but not PA-induced, hepatotoxicity. This is the first report of a cell line, animal, and clinical trial confirming that the metabolite 5-OH-PA is responsible for PZA-induced hepatotoxicity.